Doping of Active Region in Long Wavelength InP-Based Transistor Lasers - Lijun Qiao; Song Liang; Hongliang Zhu; Wei Wang (IEEE Photonics Journal)
The effects of doping in the multiquantum well (MQW) active region on the properties of InP-based long wavelength deep ridge transistor lasers (TLs) are numerically studied. Doping in the MQWs is shown to lead to a decrease of the slope efficiency and a notable increase of the current gain of the TLs, which makes MQW doping a useful tool for facilitating the design of TLs. When there are nonradiative recombination centers on the exposed MQW side walls of the TLs, doping in the MQWs is found to be able to enhance the performance of the TLs by reducing the threshold current and increasing the current gain greatly. With doping in the MQWs, the carrier diffusivity is decreased, making the defects less effective in consuming the carriers. The results show that doping in the MQWs helps to obtain high-quality TLs. The reduced carrier diffusion that results from doping also helps to improve the quality of a normal diode laser in case a deep ridge structure is needed.